Hyperhomocysteinemia as a model of VCID: Development of new models and analysis methods/behavioral models. (7th December 2020) - Weekman, Erica M.; Lee, Tiffany; Price, Brittani R.; Woolums, Abigail E.; Hawthorne, Danielle; IV, Charles E. Seaks; Wilcock, Donna M.
Abstract: Background: Vascular contributions to cognitive impairment and dementia (VCID) are increasingly recognized as a significant cause of dementia. Furthermore, VCID co‐morbid with Alzheimer's disease (AD) is estimated to occur in at least 60% of AD cases. While the contribution of VCID to clinical dementia is increasingly recognized, the mechanistic underpinnings of VCID has been lacking. Method: We have previously shown that induction of hyperhomocysteinemia (HHcy) via diet in both wildtype (WT) and APP/PS1 mice produces cerebrovascular pathologies. While the pathological characteristics of HHcy have been identified in both models, the time course for these changes is unclear. We examined neuropathological changes along a time course of 2, 4, 6, 10, 14 and 18 weeks on diet in our models. Result: In both the WT and APP/PS1 mice on the HHcy diet, increased microglial staining began at 6 weeks and was accompanied by a significant increase in several pro‐inflammatory markers. Several astrocytic end feet markers were significantly decreased at 10 weeks in the WT mice on HHcy diet. Cognitive decline also began at 10 weeks on diet in both models. Prussian blue staining revealed a significant increase in microhemorrhages starting at 14 weeks on the HHcy diet. Finally, in the co‐morbidity model, induction of HHcy resulted in redistribution of amyloid from the parenchyma to the vasculature starting at 14 weeks on diet. Conclusion: Overall, induction of HHcy in both WT and APP/PS1 mice leads first to neuroinflammation, followed by astrocytic end foot disruption and cognitive decline, and finally, microhemorrhages, and redistribution of amyloid to the vasculature in the APP/PS1 mice. Taken together, this data suggests that neuroinflammation is an initiator in HHcy mediated VCID alone and when amyloid plaques are present, providing a possible common target for therapeutics in both VCID and co‐morbid patients.